Transition of Students from Boarding High Schools to Universities in the North West Region of Cameroon Implication for Academic Achievement - Lum Bobga Jacqueline Achiri (International Journal on Integrated Education, 2022)
The study examined how transition of students from boarding high schools to public Universities influenced academic achievement in terms of Grade point Average (GPA). It explored the life style indicators of these students while in the University of Bamenda specifically, involvement in extracurricular “social” activities and absence from classes by students who leave boarding schools to the University and academic achievement. The survey research design was used in this study. A questionnaire (Likert scale) instrument was used to collect data from year 2 and 3 students in the University of Bamenda. Significant transition indicators of life style that is, focus on extracurricular (social) activities and absenteeism indicators were examined to see how they influenced academic achievement year one in the university. The random simple sampling and purposive sampling methods were used to select 204 students who provided data for the study. Data was processed and analyzed using SPSS version 21. The results showed that students who left boarding high schools to public Universities had a lower achievement rate as compared to their counterparts who left day schools. The t-test of 0.028* which was lower that the alpha level of 0.05 was indicative. This low academic achievement was influenced by two factors that is absenteeism with a mean overall score of absenteeism with a mean overall score of 2.69 and involvement in extracurricular social activities with a mean overall score of 2.65. It was therefore recommended that while in high school students should be informed on the expectations and functioning of Public Universities especially in areas of lifestyle which involve extracurricular activities, patterns of engagement with classroom work and class attendance. The university authorities should in put in place a facility for continuous counselling and follow-up of students upon entry into the university milieu.